Pengaruh Lokasi, Kualitas Produk Dan Personal Branding Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Sandang Ayu Kecamatan Pandaan Kabupaten Pasuruan) - Muchammad Aktabaroni; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the location, product quality and personal branding on purchasing decisions in case studies of consumers of Sandang Ayu, Pandaan District, Pasuruan Regency. The type of research used is the quantitative method. The sampling technique uses probability sampling with simple random sampling. Sample calculations in this study used the Malhotra formula which produced 110 respondents. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. The results showed that location, product quality and personal branding simultaneously had a positive and significant effect on purchasing decisions. Partially location, product quality and personal branding have a positive and significant effect on purchasing decisions. Keywords: Location, Product Quality, Personal Branding And Purchasing Decisions